The role of exosomes derived miRNA in cancer - Shahid Hussain; Syeda Eeman Zahra Bokhari; Xing Xing Fan; Shaukat Iqbal Malik (Journal of the Pakistan Medical Association, 2021)
Exosomes are 20-150 nm cell secreting nano-bodies that help in the transportation of various biomolecules including miRNA in the human body during both normal and diseased conditions. We aimed to summarize the role of miRNA carried by circulatory exosomes in cancer. miRNAs are responsible for contribution in cancer, regulation of gene expression, interfering in biological pathways, gene silencing or amplification and also its role in cancer resistance. miRNAs play a dynamic role in this process by regulating the genes related to drug resistance, cell proliferation, cell cycle, and apoptosis, through a tissue-specific fashion. Owing to its significances, miRNAs have been reported to be the key regulators of cancer, metastasis and also a factor in cancer resistance, and are a better source of possible potential diagnostic biomarkers. Continuous...